New species of trichomycterus (Teleostei: Siluriformes) from the andean cordillera of Argentina and the second record of the genus in Thermal Waters - Fernandez, Luis Alfredo (2012)
Trichomycterus minus, new species, is described from an Andean stream in Provincia de Catamarca, Argentina. The new species is distinguished from congeners by the number of supraorbital pores, the form of the supraorbital canal within the frontal, the length of the lateral line canal, the shape of the supraorbital tendon bone, the size of the premaxilla, the form of the barbels, an absence of a thick layer of rugose fatty tissue on the head and body, the number and degree of exposure of odontodes on the interopercle, the limited compression of the caudal peduncle, details of pigmentation, the number of premaxillary tooth rows, and the head form from a dorsal view. Trichomycterus corduvensis is recorded from thermal waters, the second locality known to be inhabited by members of the genus.